DFT based assay for tailor-made terpyridine ligand-metal complexation properties - Joshi, Krati; Krishnamurty, Sailaja; Singh, Iksha; Selvaraj, Kaliaperumal (Molecular Simulations, 2016)
Electron-rich terpyridine ligand and its metal complexes have a potential to grow as responsive surfaces by adapting their physicochemical properties as a function of environment. The responsiveness is brought about by judicious molecular level designing that is currently hindered due to lack of information and control on terpyridine (TPy)-metal (M) interactions at single molecule level. So far there is no organised understanding on the binding of different metals with TPy ligand and ways to modulate it. Being a large conjugated [GRAPHICS] system, TPy has a large scope to be functionalised with electron exchanging groups to alter its electronic structure and consequently its binding with metal atoms. In first report of such a kind, using density functional theory (DFT), we demonstrate that convenient modulation of TPy-M binding is possible through functionalisation of TPy for [GRAPHICS] , Ru, Fe, Mo and Au. Electron donating groups viz., CH [GRAPHICS] , OCH [GRAPHICS] , C [GRAPHICS] H [GRAPHICS] , NH [GRAPHICS] and electron withdrawing groups viz., CF [GRAPHICS] , COOH, CN and NO [GRAPHICS] are considered for functionalisation of TPy ligand. Significantly, the present work focuses on the functionalisation at 4 and 4 [GRAPHICS] positions of TPy molecule. The role of such a functionalisation in influencing the ligands structure-property correlation is missing in the literature to the best of our knowledge. The present investigation quantifies that by pertinent functionalisation of TPy, TPy-M binding energies can be modified up to [GRAPHICS] 60kcal/mol. Our results reveal that functionalisation leads to a considerable charge redistribution within the TPy-M complex with carbon atoms in pyridine rings functioning as major electron sink/source with a corresponding red/blue shift of [GRAPHICS] stretching frequency. This modifies the red-ox, optical and other chemical properties of TPy-M complexes. In brief, the present report illustrates a way to design ligands such as TPy for diverse applications through tailor-made functionalisation using electronic structure methodology.
Keywords: Binding energy; charge redistribution; Density functional theory; functionalisation; Metal organic complexes; metal-ligand interactions; terpyridine

Molecularly engineered graphene oxide anchored metal organic assembly: an active site economic bi-functional electrocatalyst - Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (FlatChem, 2021)
Low-temperature fuel cells are the most promising sustainable energy technology as they use hydrogen, an environmentally clean fuel. However, the sluggish kinetics of oxygen electrochemistry, a chronic issue, is holding them from commercialization. Herein, we address this issue through a molecular level design of a Graphene oxide anchored Metal Organic Molecular Assembly (G-MOMA) based catalyst. This non-precious metal catalyst consists of Ni and Fe ions ligated by graphene oxide supported terpyridine, a unique molecular assembly design that maximizes the utilization of active metal centers. This G-MOMA catalyst brings down an over potential (240 mV) for oxygen evolution reaction (OER) as close as that of the bench mark catalyst Ru/C with an impressive Tafel slope of 58 mV/dec and a cyclic stability of >30,000 cycles. G-MOMA excels in oxygen reduction reaction (ORR) too with an onset at 0.88 V (vs RHE). The remarkably stable G-MOMA catalyst surprises with an excellent bi-functionality towards both OER and ORR with an overall potential difference of mere 0.77 V, which is 180 mV and 70 mV lesser than the standard Pt/C and Ru/C catalysts, respectively. The G-MOMA catalyst is well in the activity range of the state-of-art bi-functional catalysts and yet cheaper by many folds.
Keywords: Bi-functional electrocatalyst; graphene oxide; Metal organic molecular assembly; Oxygen Evolution Reaction; oxygen reduction reaction; terpyridine